(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the levels of perceived stress, serum cortisol, and thyroid hormones (TSH, T3, and T4) in pregnant and non-pregnant women in a Pakistani population. Study Design: A case control comparative study Place and Duration of Study: This study was conducted at the Department of Physiology, Khyber Medical University, Peshawar from February to July 2024. Methods: The Perceived Stress Scale (PSS) was used to measure stress levels. Blood samples were collected to analyze cortisol, TSH, T3, and T4 levels. Independent t-tests were used to compare the groups. Independent samples t-tests were performed to compare the mean differences in hormonal levels and PSS scores between the two groups. A p-value of <0.05 was considered statistically significant. Results: Pregnant women exhibited significantly elevated cortisol levels (p = 0.001) and higher PSS scores (p = 0.007) compared to non-pregnant women. No significant differences were observed in TSH levels (p = 0.2), while T4 levels were significantly higher in pregnant women (p = 0.002). T3 levels showed no significant differences (p = 0.144). Conclusion: In pregnant women experience higher perceived stress and elevated cortisol levels. The increased T4 levels in pregnant women point out physiological changes related to pregnancy. These findings emphasized the need for stress management and hormonal monitoring in prenatal care.